Study of Salmonella Typhimurium Infection in Laying Hens - Pande, Vivek V.; Devon, Rebecca L.; Sharma, Pardeep; McWhorter, Andrea R.; Chousalkar, Kapil K. (Frontiers in Microbiology, 2016)
Members of Salmonella enterica are frequently involved in egg and egg product related human food poisoning outbreaks worldwide. In Australia, Salmonella Typhimurium is frequently involved in egg and egg product related foodborne illness and Salmonella Mbandaka has also been found to be a contaminant of the layer farm environment. The ability possessed by Salmonella Enteritidis to colonise reproductive organs and contaminate developing eggs has been well described. However, there are few studies investigating this ability for Salmonella Typhimurium. The hypothesis of this study was that the Salmonella Typhimurium can colonise the gut for a prolonged period of time and that horizontal infection through feces is the main route of egg contamination. At 14 weeks of age hens were orally infected with either S. Typhimurium PT 9 or S. Typhimurium PT 9 and Salmonella Mbandaka. Salmonella shedding in feces and eggs was monitored for 15 weeks post infection. Egg shell surface and internal contents of eggs laid by infected hens were cultured independently for detection of Salmonella spp. The mean Salmonella load in feces ranged from 1.54 to 63.35 and 0.31 to 98.38 most probable number/g (MPN/g) in the S. Typhimurium and S. Typhimurium + S. Mbandaka group respectively. No correlation was found between mean fecal Salmonella load and frequency of egg shell contamination. Egg shell contamination was higher in S. Typhimurium + S. Mbandaka infected group (7.2% Typhimurium, 14.1% Mbandaka) compared to birds infected with S. Typhimurium (5.66%) however, co-infection had no significant impact on egg contamination by S. Typhimurium. Throughout the study Salmonella was not recovered from internal contents of eggs laid by hens. Salmonella was isolated from different segments of oviduct of hens from both the groups, however pathology was not observed on microscopic examination. This study investigated Salmonella shedding for up to 15 weeks p.i which is a longer period of time compared to previously published studies. The findings of current study demonstrated intermittent but persistent faecal shedding of Salmonella after oral infection for up to 15 weeks p.i.. Further, egg shell contamination, with lack of internal egg content contamination and the low frequency of reproductive organ